Upaya Pemberantasan Perompakan dan Perampokan Laut Berdasarkan Hukum Internasional - Muhammad Ramdhan Salsabila (Justice Amnesty Law and Undoing Journal, 2025)
Piracy occurs in strategic routes, such as international trade routes or better known as international waters. The principle of universal jurisdiction can be used by a country in combating this piracy, it has been affirmed in the United Nations Convention on the Law of the Sea (UNCLOS 1982) and Indonesia has ratified it. But piracy and sea burglary remain an unresolved issue. The purpose of this research is to know the form of government implementation to universal jurisdiction principle about eradication of maritime piracy crime in Indonesia and to know preventive steps undertaken by the government in protecting Indonesian-flagged vessels in a territorialwaters prone to armed robbery. This research is done by empirical law research method by using ground theory research method. In this study also supported by secondary data through literature study. Data analysis technique used qualitative data analysis in the form of descriptive. The result of this research is that Article 4 of Indonesian Criminal Code has been able to apply its universal jurisdiction but in doing so it is necessary to consider the security and availability of resources. The preventive measures that the Government has taken to prevent regional maritime robberies are to establish the Western Fleet Quick Response Team and establish cooperation with the surrounding country in securing the border areas.